Caring for Preterm Infants with Enteral Tube Feeding - Maipimai, Maneerat (Journal of Vongchavalitkul university, 2021)
The sucking, swallowing, and breathing in the preterm infants are not well coordinated due to neurological immaturity, causing them a difficulty in suckling. Enteral tube feeding is helping preterm infants get enough nutrients to meet their nutritional needs. It is a common nursing activity in a sick newborn ward. If nurses do not perform care correctly or lack of awareness in each step, the preterm infants may be at risk of complications. The most common complication is aspiration pneumonia. Therefore, nurses require to have knowledge, skills, and awareness in all steps of enteral tube feeding to reduce the possibility of those risks, increase safety for the premature infants with enteral tube feeding, leading to an effective care outcome, and cost reduction for the medical treatment.